APPLICATION OF THE REASON MODEL WITHIN RISK MANAGEMENT ON RAILWAY CROSSINGS – A CASE STUDY - Eva NEDELIAKOVA; Lenka LIZBETINOVA; Renata STASIAK-BETLEJEWSKA; Adrian SPERKA (Scientific Journal of Silesian University of Technology. Series Transport)
Despite constant efforts to improve safety in the railway environment, various accidents and incidents happen, resulting in material damage and in the worst case, loss of human lives. This article emphasises the need for proper identification of risks, their constant monitoring, and evaluation of all causes that arise at railway crossings. Furthermore, this paper aims to apply the Reason model to the problems of railway crossings within the case study on the railway network in Slovakia. The timeliness of the problem lies in the possibility of preventing such issues in the operation of rail transport using this model. Prevention is an effective way of averting the serious consequences of accidents in the future.